STRATEGIES FOR STRENGTHENING ACADEMIC AND NON-ACADEMIC EXCELLENCE THROUGH THE INTERNALIZATION OF CULTURAL VALUES AT MAN 2 MATARAM CITY - Ardi; Muhammad; Ahyar (PT. Jurnal Center Indonesia Publisher, 2025)
This study analyzes the strategies for internalizing cultural values at MAN 2 Kota Mataram and their contribution to educational quality. The study is based on the strategic role of madrasahs in integrating religious, academic, and social dimensions as a response to globalization and character crises. A descriptive qualitative method was applied, using in-depth interviews, participatory observation, and documentation, analyzed through the Miles, Huberman, and Saldaña model. The findings reveal that religious values are reinforced through routine religious activities, discipline is enhanced by school regulations and digital attendance systems, academic culture is promoted through advanced classes and competitions, and social responsibility is cultivated through community service programs. Visionary leadership of the principal was found to be the dominant factor ensuring the consistency of these implementations. The study concludes that internalizing madrasah cultural values fosters positive habitus, enhances educational quality, and provides a replicable model for other institutions. Its contribution lies in strengthening the literature on Islamic education management by offering an integrative, culture-based approach to quality development.